KLAIM HALAL DAN MAKNA HIJRAH PADA IKLAN PRODUK HALAL DALAM PERSPEKTIF IBU-IBU MUSLIMAH - Alma Mandjusri (Avant Garde, 2017)
This research aims to identify the participatory interpretation of Moslem mothers as theaudience of the halal’s product advertisement. The theory used in this research isreception analysis to see how the media and audiences interact with one another as theagent. The research object is the TV commercial of Total Almeera – the first halaldetergent in Indonesia. The technique of data collection is by conducting a FocusGroup Discussion consisted of Moslem mothers and career educators. The results of theresearch found that most participants indicate the position of the dominant (hegemonicreading) which contained beliefs as adherents of Islam. Being a small percentage ofparticipants indicating position negotiated reading or basically received but felt halal isnot enough before there is no guarantee of passes the test for sensitive skin. As for themeaning of "hijra", most of the participants indicate the position of the dominant(hegemonic reading) that the participants feel savvy and familiar with the word Hijra.While a small percentage of participants indicating position of opposition (counterhegemonic reading), or reject the use of the concept of hijrah on TV commercial since itassumes not all moslems audience.